THE FREQUENCY OF VISITS PROVIDES A KNOWLEDGE EFFECT ON DANGER SIGNS OF PREGNANCY - Deswita Puteri, Mahfuzhah; Wulandatika, Darmayanti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Antenatal care is an effort so that the mother until the end of pregnancy is as healthy or healthier than before pregnancy and any pregnancy complications can be prevented or detected early and given adequate management. The purpose of this study was to determine the relationship between ANC frequency and pregnant women's knowledge of the danger signs of pregnancy at PMB Banjarmasin. Methods: This type of research is analytic correlation with a cross sectional approach. The research population is pregnant women as many as 68 mothers. A sample of 34 mothers with purposive sampling technique. The independent variable in this study was the frequency of ANC, while the dependent variable was the knowledge of pregnant women about the danger signs of pregnancy. Data analysis using chi-square Results: the frequency of ANC according to the minimum standard of the ANC program was 70.6% had high knowledge about danger signs of pregnancy and those who performed ANC that did not meet the standard of 64.7% had less knowledge about danger signs of pregnancy. Conclusions: There is a relationship between the frequency of ANC and the knowledge of pregnant women about danger signs of pregnancy. The p value was 0.039.